The sensitivity of Cook Glacier, East Antarctica, to changes in ice-shelf extent and grounding-line position - Jordan, Jim; Gudmundsson, Hilmar; Jenkins, Adrian; Stokes, Chris R.; Miles, Bertie W. J.; Jamieson, Stewart S. R. (Journal of Glaciology, 2022)
The Wilkes Subglacial Basin in East Antarctica contains ice equivalent to 3–4 m of global mean sea level rise and is primarily drained by Cook Glacier. Of concern is that recent observations (since the 1970s) show an acceleration in ice speed over the grounding line of both the Eastern and Western portions of Cook Glacier. Here, we use a numerical ice-flow model (Úa) to simulate the instantaneous effects of observed changes at the terminus of Cook Glacier in order to understand the link between these changes and recently observed ice acceleration. Simulations suggest that the acceleration of Cook West was caused by a retreat in calving-front position in the 1970s, potentially enhanced by grounding-line retreat, while acceleration of Cook East was likely caused by ice-shelf thinning and grounding-line retreat in the mid-1990s. Moreover, we show that the instantaneous ice discharge at Cook East would increase by up to 85% if the whole ice shelf is removed and it ungrounds from a pinning point; and that the discharge at Cook West could increase by ~300% if its grounding line retreated by 10 km.